Assessing the host range of Anastatus orientalis, an egg parasitoid of spotted lanternfly (Lycorma delicatula) using Eastern U.S. non-target species - Broadley, Hannah J.; Sipolski, Steven J.; Pitt, Danielle B.; Hoelmer, Kim A.; Wang, Xiao-yi; Cao, Liang-ming; Tewksbury, Lisa A.; Hagerty, Tyler J.; Bartlett, Charles R.; Russell, Alana D.; Wu, Yunke; Davis, Shannon C.; et al. (Frontiers in Insect Science, 2023)
The spotted lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae), an invasive planthopper discovered in Pennsylvania, U.S. in 2014, has spread to many surrounding states despite quarantines and control efforts, and further spread is anticipated. A classical (importation) biological control program would contribute to the long-term management of L. delicatula in the eastern U.S. In its native range of China, Anastatus orientalis (Hymenoptera: Eupelmidae), an egg parasitoid, causes significant mortality. Anastatus orientalis consists of multiple haplotypes that differ in important biological parameters. To delineate the physiological host range of A. orientalis Haplotype C, we completed no-choice and choice testing. No-choice testing of non-target eggs from 36 insect species spanning six orders and 18 families showed that physiologically this haplotype of A. orientalis can develop in a variety of host species eggs from the families Coreidae, Fulgoridae, Pentatomidae, and Saturniidae. For egg species that were attacked in the no-choice tests, we also conducted choice tests. Ten of the 16 species that were attacked in the no-choice tests were also attacked in the choice tests. The production of progeny on non-target egg masses was significantly lower than the production of progeny on the controls (L. delicatula egg masses run simultaneously) in the no-choice and choice tests. For the non-target species that were attacked and resulted in female wasp progeny, these females were able to produce their own progeny at the same rate as control females that were reared from the L. delicatula eggs. In general, larger host eggs corresponded to an increased female-biased sex ratio of the progeny, suggesting that gravid females select them for fertilized eggs. Results from these studies suggest that A. orientalis Haplotype C prefers to parasitize L. delicatula egg masses but is capable of developing in some non-target species.